Human navigation inside complex buildings: using instructions and maps to reach an area of refuge. Issue 2 (2nd April 2016) - Carattin, Elisabetta; Meneghetti, Chiara; Tatano, Valeria; Pazzaglia, Francesca
Abstract: Finding a safe place inside a building in an emergency can be a difficult task for disabled people, as they are expected to be able to find an "Area of Refuge" (AR) and wait there until rescued. Wayfinding is influenced by building features and type of instructions given. Two studies were carried out with the aim of exploring how the type of instructions affects wayfinding. In Studies 1 and 2, participants accompanied a wheelchair-bound friend inside a virtually reproduced medical clinic and once they reached a target zone, a fire alarm was sounded. Participants received either general instructions on how to behave in the event of a fire emergency, or specific instructions focusing on how to reach an AR, or no instructions (Studies 1 and 2); or alternatively they could look at a map or receive specific instructions accompanied by a map (Study 2). The results showed that participants who were given no instructions looked for more means of escape, and took more time to reach the AR than the other groups. In addition, this group also performed more actions during the pre-movement time. These findings highlight the importance of correct information in influencing wayfinding performance and suggest novel design solutions. The design of our study made it possible to examine not only the effect of different instruction types but also of different building features.